Cracking iPhone and Android Native Development Cross-Platform Mobile Apps Without the Kludge - Baxter-Reynolds, Matthew; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2010)
You've developed a killer app for one mobile device—now it’s time to maximize your intellectual investment and develop for the full spectrum of mobile platforms and devices. With Cracking iPhone and Android Native Development, you’ll learn how to quickly retool between the iPhone and Android platforms and broaden the interest and audience of your app, without working with burdensome and error-prone compatibility layers and toolkits. Cracking iPhone and Android Native Development takes you, the developer, through the same mobile software development project on both platforms, learning the differences between and the relative strengths and weaknesses of each platform as you go. No magic intermediate layers of obfuscation—by the time you get to the end, you'll be an expert at developing for any of the major smartphone platforms using each vendor's preferred toolset and approach. Cracking iPhone and Android Native Development covers the iPhone and Android platforms, two of the hottest mobile device platforms on the market today.
The Six Bookmarks Server Service -- Application Architecture and Functional Specification -- Android: Installing the Toolset -- Android: Building the Logon Form and Consuming REST Services -- Android: An ORM Layer on SQLite -- Android: Pushing Changes to the Server -- iOS: Installing the Toolset -- iOS: Building the Logon Form and Consuming REST Services -- iOS: An ORM Layer on SQLite -- iOS: Pushing Changes Back to the Server -- iOS: MonoTouch.
Keywords: Mobile computing; Application software; Mobile Computing; Computer Applications